Analisis Kinerja Keuangan Ditinjau dari Rentabilitas, Likuiditas dan Solvabilitas pada Peternakan Puyuh Petelur - Hidayatai Cahyani Eka Putri; Dumadi; Titi Rahmawati; Roni; Anisa Sains Kharisma (Journal of Accounting and Finance (JACFIN), 2021)
This study aims to analyze the financial performance of laying quail farms in Bulakamba District, Brebes Regency from January to December 2020 in terms of rentability, liquidity, and solvency. This research uses descriptive and qualitative analysis methods, focusing on the financial performance of animal husbandry. Based on the research, the results of the research obtained are that Mr. Roni's farm has a fairly good performance, a rentability level of 0.70 and a liquidity level of 1.60 and for the calculation of a solvency ratio level of 0.63% which is too high, when compared to the calculation of the solvency ratio of other breeders. Mr. Aripin's farm has excellent performance, rentability level of 0.76 and liquidity level of 2.19 and for the calculation of solvency ratio level of 0.49% which is lower when compared to the calculation of solvency ratio of other breeders. Mr. Raste's farm has a fairly good performance, a rentability level of 0.72 and a liquidity level of 1.67 and for the calculation of the solvency ratio rate of 0.61%. Mr. Kito's farm has a fairly good performance, a rentability level of 0.69 and a liquidity level of 1.63 and for the calculation of a solvency ratio of 0.57% which is lower when compared to the calculation of the solvency ratio of other breeders. Mr. Jeri's farm has a fairly good performance, a rentability level of 0.63 and a liquidity level of 1.62 and for the calculation of a solvency ratio of 0.63% which is slightly higher when compared to the calculation of the solvency ratio of other breeders.